Cissus quadrangularis inhibits IL -1β induced inflammatory responses on chondrocytes and alleviates bone deterioration in osteotomized rats via p38 MAPK signaling - Kanwar, Jagat R; Samarasinghe, Rasika M; Kumar, Kuldeep; Arya, Ramesh; Sharma, Sanjeev; Zhou, Shu Feng; Sasidharan, Sreenivasan; Kanwar, Rupinder K (Dove Medical Press, 2015)
Introduction: Inflammatory mediators are key players in the pathogenesis of osteoarthritis (OA) and bone destruction. Conventional drugs suppress symptomatic activity and have no therapeutic influence on disease. Cissus quadrangularis and Withania somnifera are widely used for the treatment of bone fractures and wounds; however, the cellular and molecular mechanisms regulated by these herbals are still unclear. Methods: We established an in vitro OA culture model by exposing human chondrocytes to proinflammatory cytokine and interleukin (IL)-1β for 36 hours prior to treatment with the herbals: C. quadrangularis, W. somnifera, and the combination of the two herbals. Cell viability, toxicity, and gene expression of OA modifying agents were examined. In addition, expression of survivin, which is crucial for cell growth, was analyzed. In vivo work on osteotomized rats studied the bone and cartilage regenerative effects of C. quadrangularis, W. somnifera, and the combination therapy. Results: Exposure of chondrocytes to IL-1β induced significant toxicity and cell death. However, herbal treatment alleviated IL-1β induced cell toxicity and upregulated cell growth and proliferation. C. quadrangularis inhibited gene expression of cytokines and matrix metalloproteinases, known to aggravate cartilage and bone destruction, and augmented expression of survivin by inhibiting p38 MAPK. Interestingly, osteotomized rats treated with C. quadrangularis drastically enhanced alkaline phosphatase and cartilage tissue formation as compared to untreated, W. somnifera only, or the combination of both herbals. Conclusion: Our findings demonstrate for the first time the signaling mechanisms regulated by C. quadrangularis and W. somnifera in OA and osteogenesis. We suggest that the chondroprotective effects and regenerative ability of these herbals are via the upregulation of survivin that exerts inhibitory effects on the p38 MAPK signaling pathway. These findings thus validate C. quadrangularis as a potential therapeutic for rheumatic disorders.